Satellite tracking of hawksbill turtles nesting at Buck Island Reef National Monument, US Virgin Islands: Inter-nesting and foraging period movements and migrations. (January 2019) - Hart, Kristen M.; Iverson, Autumn R.; Benscoter, Allison M.; Fujisaki, Ikuko; Cherkiss, Michael S.; Pollock, Clayton; Lundgren, Ian; Hillis-Starr, Zandy
Abstract: To conserve imperiled marine species, an understanding of high-density use zones is necessary prior to designing and evaluating management strategies that improve their survival. We satellite-tracked turtles captured after nesting at Buck Island Reef National Monument (BIRNM), St. Croix, US Virgin Islands to determine habitat-use patterns of endangered adult female hawksbills ( Eretmochelys imbricata ). For 31 turtles captured between 2011 and 2014, switching state-space modeling and home range analyses showed that inter-nesting (IN) core-use areas (i.e., 50% kernel density estimates [KDEs]) were 9.6 to 77.7 km 2 in area, occupied for 21 to 85 days, and in shallow water (21 of 26 centroids > −10 m). The IN zones overlapped with areas both within the protected borders of BIRNM, and outside BIRNM (32% of turtle-tracking days outside during IN). Turtles migrated to their foraging grounds between July and October with path lengths ranging from 52 to 3524 km; foraging areas included 14 countries. Core-use foraging areas (50% KDEs) where turtles took up residence were 6.3 to 95.4 km 2, occupied for 22 to 490 days, with mean centroid depth − 66 m. Our results show previously unknown habitat-use patterns and highlight concentrated areas of use both within and adjacent to a US protected area during the breeding season. Further, our results clearly demonstrate the need for international conservation to protect hawksbills, as migrating turtles crossed between two and eight different jurisdictions. Our results provide critical spatial and temporal information for managers charged with designing strategies to minimize human impact to and maximize survival for this globally imperiled species. Highlights: Satellite-tracking 31 adult female hawksbills revealed key habitat-use information. Inter-nesting home ranges (47.3–440.9 km 2 ) were occupied for 21–85 days. Migration paths were up to 3524 km. Foraging sites were located in 14 different countries. Detailed temporal and spatial hawksbill habitat-use data are critical for managers.